Recent Progress in Vaccine Development Against Chikungunya Virus - Gao, Shan; Song, Siqi; Zhang, Leiliang (Frontiers in Microbiology, 2019)
Chikungunya fever (CHIKF) is an acute infectious disease that is mediated by the mosquito-transmitted chikungunya virus (CHIKV). People infected with CHIKV may experience high fever, severe joint pain, skin rash, and headache. In recent years, this disease has become a global public health problem. However, there is no licensed vaccine available for CHIKV. Accumulating research data have provided novel approaches and new directions for the development of CHIKV vaccines. Our review focuses on recent progress in CHIKV vaccine studies. The potential vaccine candidates are classified into seven types: inactivated vaccine, subunit vaccine, live-attenuated vaccine, recombinant virus-vectored vaccine, virus-like particle vaccine, chimeric vaccine, and nucleic acid vaccine. These studies will provide important insights into the future development of CHIKV vaccines.